Retrospective evaluation of the survival rate of single tooth prostheses supported in external hexagonal implants: mean follow-up of 9 years - Carolina Accorsi CARTELLI; Ivete Aparecida de Mattias SARTORI; Geninho THOMÉ; Ana Cláudia Moreira MELO
Abstract Introduction The use of osseointegrated dental implants for the rehabilitation of patients has revolutionized dentistry. Objective To retrospectively evaluate the survival rate and the frequency of complications with external hexagon platform supporting single crowns. Material and method Dental forms of 110 patients who received 143 implants at the Ilapeo College (2004-2015) were used. The variables were: age, gender, systemic involvement at the time of surgery, region, implant design, type of surface, fixation system, pillar type and prosthesis material. The outcome variables were the incidence of complications in the implant or prosthesis and time in use. The mean follow-up period was 9 years. Result 32.8% had some systemic disease. Ninety-six implants (67.1%) were installed in the maxilla and 47 (32.9%) in the mandible, 87 (60.8%) were in the posterior region and 56 (39.2%) in the anterior region, while 40 (28%) were placed in regions that had received bone reconstruction. The majority (97.2%) of the implants presented surface treatment, 42% had a cylindrical design and 58% were tapered. The majority of the prosthetic components (89.6%) used were UCLAs and most of the prostheses were fused-to-metal (79.7%). The rate of prosthetic complications was 19.58% and three implants had been lost (97.9% survival rate). There was no statistical difference between the variables analyzed for both the occurrence of prosthetic complications and for the loss of the implant. Conclusion Implants with external hexagon connection were an effective and predictable option to support crowns and had high survival rates.